NILAI THIOBARBITURIC ACID (TBA) DAN KADAR LEMAK DENDENG DAGING KAMBING YANG DIRENDAM DALAM JUS DAUN SIRIH (Piper betle L.) PADA KONSENTRASI DAN LAMA PENYIMPANAN YANG BERBEDA - Endah Purnamasari; Nurhasni Nurhasni; Wieda Nurwidada Haritsah Zain (Jurnal Peternakan, 2012)
This research was conducted from December 2011 until April 2012 in Post-Harvest Technology Laboratory, Laboratory Nutrition Science and Chemistry Faculty of Agriculture and Animal Science of Islamic State University of Sultan Syarif Kasim Riau and Chemical Fisheries Product Laboratory of Fisheries and Marine Sciences Faculty of Riau University. This study aims to determine the effect of soaking dried meat (dendeng) goat in juice of betel leaves to TBA and fat value with different concentration and storage time. The research used a Completely Randomzed Design with 2 x 2 factorial with two replications. The factors were concentration of betel leaf juice (0%, 10%, 20%, 30% and 40%) and storage time (0, 1, 2, 3 and 4 months). Observed variables were the TBA score and fat of dried goat meat (dendeng). The results indicated that dried meat goat (dendeng) soakied in the juice of betel leaves and storage time influence significantly (P< 0.05) on TBA score and fat of dried meat goat. The best result was soaking dried meat goat (dendeng) on 20% of betel leaf juice during 1 months storage